KUNTOWIJOYO DAN KEBUDAYAAN PROFETIK - Qodir, Zuly (Profetika, 2015)
Kuntowijoyo as a historian, Muslim scholar, and author, is undeniable about his abilities. The most phenomenal from Kuntowijoyos literary work, as a cultural work is his idea on prophetic literature. Prophetic literature is Kuntowijoyos original work based on three edicts, they are: structural transendental epistemology, humanization and interrelation among awareness ended in liberation. His formulation on the three edicts of prophetic literature that made Kuntowijoyo to be an author, not only an author who created literary and cultural works as culture, but also as worship. All cultural activities are worships, because they are forms of subjecting to the Creator and faith to Allah. In Kuntowijoyos view, in order to be in advance, Muslim community must leave the myth and ideology world toward the knowledge world, therefore, Islamic knowledge is necessary, not Islamization of knowledge.